(untitled) (Economic and Political Thought, 2013)
The article is an attempt to answer a question about the role of the Euro- -Atlantic system in the multi-polar international order and whether it will be able to guarantee peace and security. Will it be able to compete with the growing power of China, India, Russia and other emerging super-powers? The author advances a thesis that it is very difficult to answer the above questions today because the world is becoming more and more unpredictable and the dynamic of the occurring changes is unprecedented. Moreover, the world is still involved in the financial and economic crisis and it is hard to say when it is going to finish and what consequences it is going to have for the United States, the European Union and other members of the contemporary international relations. The author shows that a new, multi-polar and multi-civilizational world order is coming into existence today and the analysis of the years 1991–2010 proves that the Atlantic Alliance was not prepared for the collapse of the bipolar system and the Soviet empire, which was believed to be the biggest threat for international peace and security. Moreover, the author wonders whether the renaissance of the Atlantic Alliance is possible and whether it can play the same role in the 21st century as it used to play under the leadership of the United States in the 20th century. He suggests that if the Atlantic Alliance manages to break the present deadlock, it will be a co-author of the new multi-polar international order. However, if it fails, the world will find itself in a long period of chaos, conflicts and wars because for dozens of years China or India will not be strong enough to create a new international peaceful order without or with marginalized participation of the Atlantic Alliance.